ANTIOXIDANT POTENTIAL FRACTIONATION FROM METHANOL EXTRACT OF AERIAL PARTS OF CONVOLVULUS ARVENSIS LINN. (CONVOLVULACEAE) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Aerial parts of Convolvulus arvensis were subjected to extraction and further fractionation to obtain antioxidant rich fraction. Different concentrations of methanolic extract and its ethyl acetate fraction were subjected to antioxidant assay by DPPH method, nitric oxide scavenging activity and reducing power assay. The fractions showed dose dependent free radical scavenging property in all the models. IC50 values for methanolic extract and its ethyl acetate fraction were found to be 131.03 ± 2.46 and 43.21 ± 4.45 respectively in comparison to L-Ascorbic acid and Rutin as standard with IC50 values of 6.537 ± 0.235 and 5.437 ± 0.206 respectively in DPPH model. In nitric oxide scavenging activity the IC50 values were found to be 130.12 ± 2.46 and 57.5 ± 4.45, 21.06 ± 0.953 and 29.93 ± 0.324 for methanolic extract and its ethyl acetate fraction, L-Ascorbic acid and Rutin respectively. The fractions showed good reducing power with increasing concentration. However, the ethyl acetate fraction showed a good reducing power and better free radical scavenging activity as compared to methanolic extract thus its antioxidant potential is comparable to standards. HPTLC analysis of ethyl acetate fraction confirms the presence of flavonoids which are responsible for the antioxidant activity. This is the first report on antioxidant activity of C. arvensis.